Theoretical and methodological foundations of the study of political communication - Uali, Б.; Gabdulina, Б.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2020)
Today, the terms political communication and public opinion are the core of political science. The article deals with the theoretical and methodological foundations of such concepts as political communication, public opinion, influence on public opinion. It also focuses on the relevance and importance of political communication and public awareness today. The positions and conceptual ideas of scientists as a mechanism of influence of political communication on public consciousness are considered and analyzed. Today we see that in the global political process, society, public consciousness, as an object, skillfully using various goals, various political technologies, receive the corresponding «product». It should be noted that the impact mechanisms can also be used for the benefit of the subject. The impact of political communication on the development of society and the mechanisms for its optimal use remain scientifically relevant today.